O cérebro na história do crime : análises acerca da evolução teórica da neurocriminologia - Quevedo, Jéssica Veleda (2021)
The following work was produced to investigate if the current neurocriminological theories are similar to those developed by Lombroso during the 19th century, in their biologizing power. That is, to observe it the arguments sustained nowadays by neurocriminologists really come close to what the Positive School preached. In that matter, the influence of such researches in Criminal Law was also investigated, since the notion of culpability is closely connected to the possibility of self determination of an individual, and because results of researches within the matter of free will seem to matter on a philosophical level to the application of Criminal Law. A qualitative approach was applied along a bibliographical outlining, in a way that writings on biological and psychological theories of crime were selected and those with pure sociological views were excluded. The outline for the selected material parted from the end of the 19th century and ended in present-day publications, to answer the research’s problem: “Are the current neurocriminological theories, despite technological evolution, similar in their biologizing and deterministic power to those of the 19th century?” Therefore, the work has been divided in two chapters – the first one presents a theoretical-historical summary of the theories of the Positive School and Biosocial Criminology from the end of the 20th century –, and the second touches the key-issue more deeply, during which an explanation about the union of neuroscience and criminology and its outspreads in modern society are explained. Denying the hypothesis, the conclusion points to the fact that, even though the origin and the focus of these researches are the same, the content produced within neurocriminology nowadays, besides not having a strong theoretical basis, are more careful remarks pointing towards the correlation between biological (brain-related) factors and behaviors socially determined as criminal (or antisocial), thus avoiding deterministic approaches. Hence, even though the hypothesis has not been confirmed by the analyzed material, it has been possible to perceive that a perspective that comprehend and embraces the biopsychological factors that influence in criminal behavior is the way to go within Criminal Sciences, allowing an holistic approach to the phenomenon of criminality.